2007
DOI: 10.1039/b709621f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled size manipulation of free gold nanoparticles by laser irradiation and their facile bioconjugation

Abstract: The average size of gold nanoparticles (AuNP), obtained by laser ablation in solution, is reduced to a few nanometers or increased to tens of nanometers using laser treatments with different strategies. The techniques do not require any stabilizing molecules and the AuNP surface is free from strongly linked ligands. This allowed one-step, immediate and very efficient functionalization of AuNP with commonly used proteins like bovine serum albumin (BSA), which can be detected, using small nanoparticles, down to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
202
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(213 citation statements)
references
References 49 publications
8
202
0
2
Order By: Relevance
“…Despite the absence of stabilizers, noble metal nanoparticles produced by laser ablation in liquid (LAL) in various media including deionized and organic solvents are anomalously stable for days and even up to several months. [68][69][70] We also confirmed that AuNPs prepared by LAL in deionized water are stable after one month without any stabilizing agents. The surfactantfree AuNPs so produced are inherently stable mainly because their surfaces are negatively charged.…”
supporting
confidence: 63%
“…Despite the absence of stabilizers, noble metal nanoparticles produced by laser ablation in liquid (LAL) in various media including deionized and organic solvents are anomalously stable for days and even up to several months. [68][69][70] We also confirmed that AuNPs prepared by LAL in deionized water are stable after one month without any stabilizing agents. The surfactantfree AuNPs so produced are inherently stable mainly because their surfaces are negatively charged.…”
supporting
confidence: 63%
“…Their average diameter was determined by fitting the UV-vis solution spectra with the Mie-Gans model, which was shown to be a simple and reliable method. [20][21][22][23] It was found that AuNP have an average diameter of 10 nm, which is small enough to be included in the interstices of opals without perturbing their structure. Polystyrene (PS) opals, both bare and AuNP doped, were grown according to the procedure previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…AuNP were prepared by laser ablation [20][21][22][23] in water solutions of sodium dodecyl sulfate (10 12 AuNP/cm 3 ). Their average diameter was determined by fitting the UV-vis solution spectra with the Mie-Gans model, which was shown to be a simple and reliable method.…”
Section: Resultsmentioning
confidence: 99%
“…A 'top-down' approach, laser fragmentation in liquid, has been normally adopted to realize size-reduction and size-distributionnarrowing of colloidal noble metal (gold and silver) nanoparticles, through nanosecond laser vaporization [15][16][17] or picosecond-laserinduced Coulomb explosion 18 of nanoparticles upon laser irradiation. However, the polydispersity after laser treatments usually remains fairly large (s410%).…”
mentioning
confidence: 99%